Epileptic crisis in a patient with obstructive sleep apnea during drug-induced endoscopy - Rodríguez-Alcalá, Laura; O´connor Reina, Carlos; Gil, Blas Rodríguez; Plaza, Guillermo; Morente, Juan Carlos Casado (Sleep Science, 2021)
Drug-induced sleep endoscopy (DISE) is a complementary method for the diagnosis of obstruction sites in patients with snoring and obstructive sleep apnea (OSA) and allows the optimization of treatment. We present the first case of a patient having a seizure during DISE, after sedation with midazolam and propofol. We recommend that DISE should be performed in a safe environment, under monitoring, and with anesthesia equipment that can be used to counteract potential complications caused by seizures.
Keywords: Drug-induced Sleep Endoscopy; Propofol; Seizures